2004
DOI: 10.1111/j.0013-9580.2004.13104.x
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Mapping of Genetic Loci Controlling Absence Epilepsy Phenotypes in the WAG/Rij Rat

Abstract: Summary: Purpose:The WAG/Rij rat is among the most appropriate models for the study of spontaneous childhood absence epilepsy, without complex neurologic disorders that are associated with some mouse models for absence epilepsy. Previous studies have allowed the identification of distinct types of spikewave discharges (SWDs) characterizing seizures in this strain. The purpose of this study was to investigate the genetic basis of electroencephalographic (EEG) properties of SWDs.Methods: An intercross was derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 47 publications
2
31
0
Order By: Relevance
“…Human absence epilepsy is associated with mutations in the genes encoding the  5 ,  3 , or  2 subunits of the GABA A receptor (Hirose, 2014) and the amount of the  3 subunit in the NRT has been shown to be reduced in WAG/Rij rats as compared to non-epileptic control rats (Gauguier et al, 2004;Liu et al, 2007); instead, GABA A receptors are preserved in the neocortex of WAG/Rij epileptic rats, which are defective in several GABA B receptor isoforms (Liu et al, 2007;Merlo et al, 2007).…”
Section: Gabamentioning
confidence: 99%
See 2 more Smart Citations
“…Human absence epilepsy is associated with mutations in the genes encoding the  5 ,  3 , or  2 subunits of the GABA A receptor (Hirose, 2014) and the amount of the  3 subunit in the NRT has been shown to be reduced in WAG/Rij rats as compared to non-epileptic control rats (Gauguier et al, 2004;Liu et al, 2007); instead, GABA A receptors are preserved in the neocortex of WAG/Rij epileptic rats, which are defective in several GABA B receptor isoforms (Liu et al, 2007;Merlo et al, 2007).…”
Section: Gabamentioning
confidence: 99%
“…Genetic analysis of this strain by quantitative trait loci (QTL) mapping demonstrated the polygenic control of SWD phenotypes, which was earlier hypothesized considering that WAG/Rij rats are a fully inbred strain from Wistar rats. Mendelian cross-breeding studies suggested that one dominant gene determines the occurrence and other genes modulate the number and duration of SWDs ; subsequently, Gauguier et al identified the above mentioned QTLs, T1swd/wag on chromosome 5 controlling type-1 SWD average duration and T2swd/wag on chromosome 9 controlling the total duration of type-2 SWDs (Gauguier et al, 2004).…”
Section: Current Limitations and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several genetic models of absence epilepsy in rodents. The most commonly used of these models are the genetic absence epilepsy rat from Strasbourg (GAERS) rat (46), Wistar albino Glaxo from Rijswijk (WAG/Rij) rats (47), and more recently, C3H/He mice (30). While these models exhibit absence seizures, their polygenic mode of inheritance makes it difficult to find the genetic mechanisms responsible for the disease.…”
Section: Is Reduced Cortical Inhibition Sufficient To Cause Absence Ementioning
confidence: 99%
“…for genetic analyses of absence epilepsy Vadász et al, 1995;Gauguier et al, 2004). These long lasting recordings are also necessary for the study of long term drug effects and epileptogenesis , for chronic drug studies (D'Amore et al, 2014), for the study of circadian rhythms of SWDs and the consequences of their shifts (Smyk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%